2013
DOI: 10.1371/journal.pone.0078714
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Protein Phosphotome of Entamoeba histolytica Reveals an Intricate Phosphorylation Network

Abstract: Phosphorylation is the most common mechanism for the propagation of intracellular signals. Protein phosphatases and protein kinases play a dynamic antagonistic role in protein phosphorylation. Protein phosphatases make up a significant fraction of eukaryotic proteome. In this article, we report the identification and analysis of protein phosphatases in the intracellular parasite Entamoeba histolytica. Based on an in silico analysis, we classified 250 non-redundant protein phosphatases in E. histolytica. The ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…The phosphatomes vary in size between genera from 482 phosphatases in Tv to 35 in Ec . The phosphatome of Eh consists of 250 phosphatases that were reported in our earlier analysis [5, 6]. There was a huge variation in phosphatome of the genera Trypanosoma .…”
Section: Resultsmentioning
confidence: 80%
See 3 more Smart Citations
“…The phosphatomes vary in size between genera from 482 phosphatases in Tv to 35 in Ec . The phosphatome of Eh consists of 250 phosphatases that were reported in our earlier analysis [5, 6]. There was a huge variation in phosphatome of the genera Trypanosoma .…”
Section: Resultsmentioning
confidence: 80%
“…Eh has the highest percentage of phosphatases followed by Lm and Cp . The percentage of phosphatome in Hs is 0.6% of its proteome (Fig 1) [5, 28], which is much less than the selected parasites phosphatomes, indicating that vertebrates have various other mechanisms for the regulation of proteins but in protozoan parasites phosphorylation is an integral mechanism for protein regulation.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It was demonstrated that the plasma membranes of Leishmania donovani , a protozoan parasite, were enriched in acid phosphatase activity, indicating the integral role of phosphatases in parasitism [ 58 ]. In our previous study, it was suggested that several phosphatases are involved in cation TM transport activity and ion channel activity [ 59 , 60 , 61 ]. Cell signaling has been found to regulate lipid phosphate phosphatases (LPPs) by adjusting the concentrations of lipid phosphates against their dephosphorylated products [ 62 ].…”
Section: Discussionmentioning
confidence: 99%